IMPLEMENTASI SOP PELAYANAN DI DINAS KOPERASI, USAHA MIKRO KECIL MENENGAH, PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN PESISIR SELATAN - Ramadhan, Rizki Mandala (Jurusan Ilmu Administrasi Negara, 2024)
Rizki Mandala Ramadhan, 1410842015, Implementation of SOP Services at the Office of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry, Pesisir Selatan Regency, Department of Public Administration, Faculty of Social and Political Sciences, Andalas University, Padang, 2021. Supervised by: Kusdarini, S. IP, M.PA and Dr. Ria Ariany, M.Si. This thesis consists of 156 pages with references to 8 theory books, 4 method books, 2 journals, 1 Thesis, 5 Regulations and 1 appendix. There are employees who do not understand or do not understand the contents of the existing Service SOP. In addition, there are also employees who work not according to the rules in the SOP, this is because the behavior and background of the employee who initially did not work according to the rules. The lack of ability of employees in using service support facilities such as computers and printers results the services provided are not optimal. Competence is indeed a fundamental problem in the service process carried out, especially competencies related to the use of service support facilities. So that the formulation of the problem in this study is